Uncertainty related to climate change in the assessment of the DDF curve parameters. (October 2017) - Liuzzo, Lorena; Notaro, Vincenza; Freni, Gabriele
Abstract: In the context of climate change, the evaluation of the parameters of Depth-Duration-Frequency (DDF) curves has become a critical issue. Neglecting future rainfall variations could result in an overestimation/underestimation of DDF parameters and, consequently, of the design storm. In this study, uncertainty analysis was integrated into trend analysis to provide an estimate of trends that cannot actually be rigorously verified. A Bayesian procedure was suggested for the updating of DDF curve parameters and to evaluate the uncertainty related to their assessment. The proposed procedure also allowed identification of the years of a series that contributed most to the overall uncertainty related to the parameter estimation. The methodology was implemented to estimate the DDF parameters for 65 sites in Sicily (Southern Italy). The results showed that the DDF parameters were affected by increases and decreases over the 1950–2008 period, with different levels of uncertainty. Highlights: Effects of climate change on DDF curve parameters. A Bayesian procedure to account for uncertainty in the estimation of DDF curve parameters. Short-term scenarios of DDF curve parameters.